Mechanism of an acceleration in T1 precipitation kinetics in an Al-Cu-Li alloy by electropulsing. (December 2021) - Zhou, Chang; Zhan, Lihua; Li, He; Chen, Fei; Liu, Guanri; Yan, Dongyang
Abstract: Effect of electropulsing has been investigated on the microstructures and precipitation kinetics of an Al-Cu-Li alloy during artificial ageing. Electropulsing assisted ageing (EAA) and conventional ageing (CA) were carried out under various ageing temperature and time conditions. The maximum stable plateau of EAA samples happens for less ageing times, than that of CA samples from ageing hardening curves. It was found that precipitation activation energy in EAA is remarkably reduced by ~45% compared to CA. Dislocation reconfiguration was firstly found to happen via electropulsing during artificially ageing. Specifically, both the larger dislocation lines and the resultant dislocation network configuration were observed in the EAA sample of ageing for 1 h. Before the peak statue, the average length and number density of T1 plates in the EAA samples were much larger than those of the CA sample at the same ageing time. Based on the results analyzed, a new mechanism, which considering the formation of dislocation network configuration induced by electropulsing and the reduced average diffusion field size via dislocation network resulting in the absorption among T1 precursors in a shorter timescale, has been established to successfully explain an accelerated T1 precipitation during ageing assisted by electropulsing. Highlights: A new mechanism is revealed on an acceleration in T1 precipitation kinetics during ageing assisted by electropulsing. T1 precipitation activation energy is remarkably reduced by ~45% via electropulsing effects. Dislocation reconfiguration was firstly found to happen via electropulsing during artificially ageing. This beneficial 3D dislocation network can result in accelerated nucleation and growth of T1 precipitates.